Advances in genetically modified neural stem cell therapy for central nervous system injury and neurological diseases - Xiangwen Tang; Peng Deng; Lin Li; Yuqing He; Jinchao Wang; Dingjun Hao; Hao Yang (Stem Cell Research & Therapy)
Abstract Neural stem cells (NSCs) have increasingly been recognized as the most promising candidates for cell-based therapies for the central nervous system (CNS) injuries, primarily due to their pluripotent differentiation capabilities, as well as their remarkable secretory and homing properties. In recent years, extensive research efforts have been initiated to explore the therapeutic potential of NSC transplantation for CNS injuries, yielding significant advancements. Nevertheless, owing to the formation of adverse microenvironment at post-injury leading to suboptimal survival, differentiation, and integration within the host neural network of transplanted NSCs, NSC-based transplantation therapies often fall short of achieving optimal therapeutic outcomes. To address this challenge, genetic modification has been developed an attractive strategy to improve the outcomes of NSC therapies. This is mainly attributed to its potential to not only enhance the differentiation capacity of NSCs but also to boost a range of biological activities, such as the secretion of bioactive factors, anti-inflammatory effects, anti-apoptotic properties, immunomodulation, antioxidative functions, and angiogenesis. Furthermore, genetic modification empowers NSCs to play a more robust neuroprotective role in the context of nerve injury. In this review, we will provide an overview of recent advances in the roles and mechanisms of NSCs genetically modified with various therapeutic genes in the treatment of neural injuries and neural disorders. Also, an update on current technical parameters suitable for NSC transplantation and functional recovery in clinical studies are summarized.